Bangladesh Country Assistance Evaluation, 2001-08 - World Bank (World Bank, Washington, DC, 2012)
Bangladesh is among the World Bank's largest International Development Association (IDA) eligible borrowers, with a country portfolio of 21 active projects and net commitment of $1.9 billion as of FY08. The Bank's strategy has been to support government efforts to improve governance as a cross-cutting goal, while also improving the investment climate and empowering the poor. IDA's strategy for Bangladesh and its program during the period 2001-08 were relevant to the country's development needs, including improving governance and promoting structural reforms in order to consolidate gains in macroeconomic performance, exports, education, and health, and improve the prospects for successful future development. Bank assistance during the FY01-08 period was delivered under the FY01 and FY06 Country Assistance Strategies (CASs) and the FY03 CAS progress report. These largely reflected the Bank's search for more effective support for Bangladesh's efforts to sustain and enhance development, even as success in increasing exports and workers' remittances reduced the country's dependence on foreign assistance, and as awareness increased that governance issues needed to be addressed more broadly.